Association between Chlamydia and routine place for healthcare in the United States: NHANES 1999-2016. - Cornelius D Jamison (Public Library of Science (PLoS), 2021)
Background The United States is experiencing a surge in Chlamydia trachomatis (CT) infections representing a critical need to improve sexually transmitted infection (STI) screening and treatment programs. To understand where patients with STIs seek healthcare, we evaluated the relationship between CT infections and the place where individuals report usually receiving healthcare. Methods Our study used a nationally representative sample from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2016. The study population is adult patients, aged 18 to 39 years in whom a urine CT screen was obtained. Logistic regression models were used to determine if location of usual healthcare was predictive of a positive urine CT screen result. Models were adjusted for known confounders including age, gender, race/ethnicity, education, and insurance status. Results In this nationally representative sample (n = 19,275; weighted n = 85.8 million), 1.9% of individuals had a positive urine CT result. Participants reported usually going to the doctor's office (70.3%), "no place" (24.8%), Emergency Department (ED) (3.3%), or "other" place (1.7%) for healthcare. In adjusted models, the predicted probability of having a positive urine CT result is higher (4.9% vs 3.2%, p = 0.022; OR = 1.58) among those that reported the ED as their usual place for healthcare compared to those that reported going to a doctor's office or clinic. Conclusions Individuals having a positive urine CT screen are associated with using the ED as a usual source for healthcare. Understanding this association has the potential to improve STI clinical and policy interventions as the ED may be a critical site in combatting the record high rates of STIs.